(untitled) (Journal of the Bangladesh Agricultural University, 2019)
Groundwater is one of the most important natural resources which plays a vital role for drinking and irrigation usages. Evaluation of groundwater quality determines its suitability for different purposes. An investigation was carried out to evaluate the quality of groundwater for irrigation and drinking usages based on the various water quality parameters. Groundwater samples were collected from forty different sites of Kazipur upazila under the district of Sirajganj during the periods from January 20 to January 28, 2018 maintaining the distance between each of two sites as more than one kilometer. Different physiochemical parameters including pH, EC, TDS, Ca²+, Mg²+, K+, Na+, Mn²+, Fe²+, CO3²ˉ, HCO3ˉ, Clˉ, SO4²ˉ and PO4³ˉ contents were analyzed. The pH values of the groundwater samples were non-problematic for irrigation as well as drinking purposes. The obtained electrical conductivity values of the samples were within the limit of 150.0 to 754.0 µS cm-1. The samples of four sites i.e., Noapara, Meghai bazar, Salabora and Drigidrota were categorized as low salinity and the rests as medium salinity, with low alkalinity hazards. Total dissolved solids varied from 65.0 to 309.0 mg L-1 which categorized the samples as freshwater and non-problematic. All the samples were identified as excellent class based on sodium adsorption ratio (range: 0.12 0.66). Based on soluble sodium percentages, 97.5% of the samples were classified as excellent. Residual sodium carbonate values (–8.60 –1.68) of the samples were suitable for irrigation. Permeability index (range: 14.78 49.73) categorized half portion of the samples as class-II and remaining as class-I which implied the samples as suitable for irrigation usages. About 10% of samples were medium hard, 70% were hard and rests were very hard in quality. Fe2+ content ranged from 0.23 to 21.75 mg L-1 with a mean value of 5.29 mg L-1. The detected Fe2+ content of 14 water samples was above the permissible limit. Mn2+ concentration (1.58 mg L-1) was considered as hazardous for long-term irrigation purpose in most of the samples because of exceeding the recommended limit (0.20 mg L-1). As per K+, Na+, Ca2+, Mg2+, HCO3ˉ, Clˉ, SO42ˉ and PO43ˉ status, all the samples can safely be used for irrigation and drinking purposes. The assessment showed high levels of Fe2+ and Mn2+ in groundwater samples that are responsible to make the groundwater unsafe for irrigation and drinking purposes. J Bangladesh Agril Univ 17(3): 309–318, 2019